2006
DOI: 10.1038/ng1916
|View full text |Cite
|
Sign up to set email alerts
|

BMP2 activity, although dispensable for bone formation, is required for the initiation of fracture healing

Abstract: Adult bones have a notable regenerative capacity. Over 40 years ago, an intrinsic activity capable of initiating this reparative response was found to reside within bone itself, and the term bone morphogenetic protein (BMP) was coined to describe the molecules responsible for it. A family of BMP proteins was subsequently identified, but no individual BMP has been shown to be the initiator of the endogenous bone repair response. Here we demonstrate that BMP2 is a necessary component of the signaling cascade tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
606
2
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 724 publications
(642 citation statements)
references
References 30 publications
27
606
2
7
Order By: Relevance
“…More germane to the observations and conclusions that we have drawn from our studies was the demonstration that bones lacking BMP2 showed that the earliest steps of fracture healing seem to be blocked. These results lead these authors to the central conclusion that although other osteogenic stimuli were still present in the limb skeleton of these BMP2-deficient mice, that they cannot compensate for the absence of BMP2 [30].…”
Section: Discussionmentioning
confidence: 96%
“…More germane to the observations and conclusions that we have drawn from our studies was the demonstration that bones lacking BMP2 showed that the earliest steps of fracture healing seem to be blocked. These results lead these authors to the central conclusion that although other osteogenic stimuli were still present in the limb skeleton of these BMP2-deficient mice, that they cannot compensate for the absence of BMP2 [30].…”
Section: Discussionmentioning
confidence: 96%
“…The plasmid used for generating the Tbx4 probe was a gift of Dr. V. Papaioannou (Columbia University, New York, NY); Rspo2, Dr. J. Yoon (Maine Medical Center, Portland, ME). Probes for Col2a1, Hoxc10, and Tgfbi were generated as previously described (Storm and Kingsley, 1996;Ferguson et al, 2003;Choe et al, 2006;Tsuji et al, 2006). Probe for Sfrp2 was generated using the following primers 5 0 -ACATTCCCAGTGGT CTCTTGT-3 0 .…”
Section: Histology In Situ Hybridization and Immunohistochemistrymentioning
confidence: 99%
“…Given the known mechanism of action of BTxA (inhibition of neurotransmitter release), we therefore speculated that the blockade of neuromuscular signaling by BTxA inhibits neuromuscular interactions integral to the osteogenic response elicited by musculoskeletal trauma. Furthermore, because fracture healing and HO share common initiating events (including inflammation and BMP signaling) [17,27,30,32], we also speculated that BTxA-induced muscle paralysis would prevent the formation of heterotopic bone. However, interpreting the precise mechanism by which muscle paralysis inhibits osteogenesis in the rat fracture model is confounded by the heterogeneity of the tissue response, soft tissue injury, and modified gait kinematics, all of which can alter the observed cellular responses.…”
Section: Introductionmentioning
confidence: 99%